Host tissue integration process in abdominal wall defect repair: a comparison of two porcine-derived grafts in a long-term study. (July 2014) - Liu, Zhengni; Yang, Zhi; Zhou, Zhiyuan; Song, Zhicheng; Wang, Huichun; Yang, JianJun; Tang, Rui; Tan, Qiang; Gu, Yan
Abstract : Background: The aim of this study was to compare the host tissue integration process and biomechanical behaviour after implantation of porcine small intestine submucosa (PSIS) and porcine acellular dermal matrix (PADM) grafts in a rat abdominal wall defect model during a long-term follow-up of 360 days. Objectives: Full-thickness abdominal wall defects were created in 40 Sprague–Dawley rats and repaired with either PSIS or PADM grafts. Rats were sacrificed at 14, 30, 90 and 360 days to evaluate the presence of herniation, infection, adhesions and changes in thickness and strength properties of the regenerated tissue at the defect site. Histopathology and immunohistochemistry were performed to evaluate the host tissue integration process assessed by the level of collagen deposition, vascularization and inflammatory host sub-chronic and chronic responses. Results: PADM grafts had greater strength in vitro (p < 0.01). Moreover, the strength of the PADM grafts integrated with the surrounding host tissues was greater than that of the PSIS grafts at 360 days postimplantation (p < 0.05). A stronger integration into the host tissue was observed for the PADM grafts, which showed oriented bands of collagen deposition intermixed with similar newly formed blood vessels compared to that of PSIS grafts after 360 days. The PADM grafts showed slower infiltration of macrophages but developed into a more heavily infiltrated tissue compared to the PSIS grafts (p < 0.05). The level of leukocyte infiltration after implantation was similar in both grafts (p > 0.05). Conclusion: PADM grafts exhibit more delayed but also more effective host integration than PSIS grafts during the 360 days following implantation, supporting the development of more robust abdominal wall strength.